PELAYANAN KEBERSIHAN DINAS KEBERSIHAN, PERTAMANAN, DAN TATA RUANG KOTA BANJARBARU - Ade Hermawan (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2023)
This research aims to: 1) to find out the hygiene services performed by the Department of hygiene, Gardening, and Spatial Banjarbaru, 2) to know the obstacles faced by the hygiene, Gardening, and Spatial Banjarbaru city janitorial service in 3) to find out a solution to overcome the obstacles faced by the hygiene, Gardening, and Spatial in-Banjarbaru City Janitorial service.This research use the method diskriftif. Data collection techniques used are interviews, observation and documentation. Samples taken with the technique of sampling aksiden with a population of 50 people. While the data analysis technique used is qualitative.Results of the study showed, 1) Services Service hygiene, Gardening, and Spatial Banjarbaru in providing services to the citizens of the community hygiene Banjarbaru include: Implementing local regulations concerning the Hygiene of the city, the transport of Waste every day, Garbage Wagon Fleet, Procurement and revenue increase a janitor. 2) obstacles faced by the hygiene, Gardening, and Spatial Banjarbaru in dealing with the issue of hygiene in areas of the city such as: place of the lack of public awareness of the meaning of cleanliness and lack of supervision by a supervisory officer in the field. 3) solution that has been Reached on the basis of constraints faced by a solution undertaken by the Department of hygiene, Gardening, and Spatial Banjarbaru to overcome problems of hygiene in the region namely: Banjarbaru Give socialization to society about the sense of the importance of hygiene service, Held the race – race hygiene and beauty of the city, Assigned to the officer's supervisor in the field to active checking and supervising janitor and hauled back trash bins are still lags behind – because society throw late in his time.